Metodologia multivariada para avaliação do risco de crédito de operações bancárias - Moura, Heber José de (1995)
The dissertation investigates the banking risk credit within the Brazilian environment. 10 the Brazilian economy, where the entrepreneur has to face an enormous instability, and the corresponding difficulties in forecasting and programming his activities are high, some particularities become extremely relevant. The traditional models and procedures appear as inadequate and new approaches had to be developed. The banking lending was analyzed using multivariate statistics methods concerning the simultaneous influence from lender, operation and economic variables. I suggest an new way to focuses the problem. An application based on data provided from Banco do Nordeste do Brazil is presented, and it determines the risk portion to be added to loan, as a function from your risk profile.